Modelagem, projeto e implementação de um conversor isolado com um único estágio e correção do fator de potência. - Ficagna, Paulo Canuto dos Santos (2008)
This Master Thesis presents a new analysis, modeling and design guideline for an Insulated Power Factor Corrected Single-Stage Converter. First, the operating principle is presented which provides a better understanding of the converter. So, based on this new analysis, the two operation modes description and the new steady-state gain of the converter are provided. A new control strategy for the input current control-loop is also proposed which provides an improvement of the total harmonic distortion (THD). The conditions to reset the magnetic flux for the high frequency transformer (HFT) into a switching period and the mitigation of the reactive energy are provided. At the sequence, the transfer functions that describe the dynamic behavior of the output voltage and the input current due to perturbations on duty-cycle and input voltage are derived. These dynamic models are derived based on the averaged equivalent circuit (AEC) obtained by modeling an equivalent DC-DC converter. Finally, the design guideline and experimental results for validation of the mathematical analysis and numerical simulation confirmation are provided.